Peran Kepastian Hukum oleh Hakim atas Penjatuhan Pidana dalam Perkara Korupsi: Analisis Putusan Nomor 7/Pid.Sus-TPK/2023/Pn Yyk (International Forum of Researchers and Lecturers, 2023)
The role of judges in forming laws and interpreting statutory texts is important to realize the value of legal certainty. Evidence in criminal justice is an important focus. Especially if there are judges who have different views and apply dissenting opinions in assessing concrete cases, especially criminal acts of corruption. The aim of this research is to analyze the views of two different panels of judges in achieving legal certainty and substantive justice received by the defendant during the criminal justice process. The research method used in this research is normative-empirical research which in collecting data uses literature and observation methods to observe and record the situation and conditions of legal events that occur. The results of this research are that judges' freedom in making decisions often ignores legal certainty due to differences in interpretation, resulting in clear laws becoming unclear and the value of legal certainty not being achieved optimally